Employment is associated with manual ability in adults with cerebral palsy – a population-based study - Hedberg-Graff, Jenny; Rodby-Bousquet, Elisabet ; 0000-0001-8373-1017; Lindgren, Anna; Manousaki, Evgenia; Cloodt, Erika; Pettersson, Katina (Disability and Health Journal, 2025)
Background: Employment rates are lower in adults with cerebral palsy (CP). Even though reduced manual ability is associated with limitations in daily activities, it is unclear whether employment rates are associated with manual ability in adults with CP. Objective: To analyze regular employment and employment rates (hours/week) in adults with CP and estimate their associations with manual ability relative to age and sex. Methods: This was a cross-sectional study of adults with CP, aged 20–64 years, from the combined Swedish CP follow-up program and registry. Manual ability was classified as levels I–V using the Manual Ability Classification System (MACS). Logistic regression analysis was used. Results: The study included 2304 adults with CP (1271 men; median age 28 years, interquartile range 20–64 years). Fewer than one in five (19 %) were employed, and about half (52 %) of these worked full time. The probability of employment in adults with MACS level II was almost half that of those with level I (OR 0.44; 95 % CI 0.34–0.57) and decreased with each MACS level to OR 0.01 (95 % CI 0.00–0.03) for MACS V. Limited manual ability was associated with a lower probability of working full time: ORs of 0.46 (95 % CI 0.30–0.72) for MACS II and 0.29 (95 % CI 0.16–0.56) for MACS III–V. Conclusion: Limited manual ability in adults with CP impacts both their likelihood of employment and employment rate. Greater manual ability is associated with a higher probability of regular employment and working full time.
Publisher Copyright: © 2025 The Authors
Keywords: Adult; Cerebral palsy; Employment; Manual ability